Hypoxic preconditioning enhances the differentiation of bone marrow stromal cells into mature oligodendrocytes via the mTOR/HIF‐1α/VEGF pathway in traumatic brain injury - Xiaoyu Yuan (Brain and Behavior, 2020)
Abstract Objective Traumatic brain injury (TBI) results not only in gray matter damage, but also in severe white matter injury (WMI). Previous findings support hypoxic preconditioning (HP) could augment the efficacy of bone marrow stromal cell (BMSC) transplantation in a TBI mouse model. However, whether HP‐treated BMSCs (H‐BMSCs) could overcome remyelination failure after WMI is unclear, and the molecular mechanisms remain to be explored. Here, we focused on the therapeutic benefits of H‐BMSC transplantation for treating WMI, as well as its underlying mechanisms. Methods In vitro, BMSCs were incubated at passage 4 in the hypoxic preconditioning (1.0% oxygen) for 8 hr. In vivo, a TBI mouse model was established, and DMEM cell culture medium (control), normal cultured BMSCs (N‐BMSCs), or H‐BMSCs were transplanted to mice 24 hr afterward. Neurobehavioral function, histopathological changes, and oligodendrogenesis were assessed for up to 35 days post‐TBI. Results Compared with the control group, improvement of cognitive functions and smaller lesion volumes was observed in the two BMSC‐transplanted groups, especially the H‐BMSC group. H‐BMSC transplantation resulted in a greater number of neural/glial antigen 2 (NG2)–positive and adenomatous polyposis coli (APC)–positive cells than N‐BMSC transplantation in both the corpus callosum and the striatum. In addition, we observed that the expression levels of hypoxia‐inducible factor‐1a (HIF‐1α), phosphorylated mechanistic target of rapamycin (p‐mTOR), and vascular endothelial growth factor (VEGF) were all increased in H‐BMSC–transplanted mice. Furthermore, the mTOR pathway inhibitor rapamycin attenuated the impact of HP both in vivo and in vitro. Conclusion The results provided mechanistic evidences suggesting that HP‐treated BMSCs promoted remyelination partly by modulating the pro‐survival mTOR/HIF‐1α/VEGF signaling pathway.